Variants and factors of catatonic syndrome pathomorphosis in the structure of endogenous catatonia - Safonov, D. M.; Сафонов, Дмитро Миколайович (Journal of Education, Health and Sport, 2018)
Pathomorphosis of mental pathology leads to polymorphism or dissociation of its clinical manifestations, and, as a result, to difficulties in identification and differential diagnosis of individual psychopathological forms.
Keywords: pathomorphism; endogenic catatonia; factors of catatonic syndrome